Quality Of Life And Stigma Among People Living With HIV/AIDS In Iran - Ebrahimi Kalan M (Dove Medical Press, 2019)
Mohammad Ebrahimi Kalan,1 Jian Han,2 Ziyad Ben Taleb,3 Kristopher P Fennie,1 Mohammad Asghari Jafarabadi,4,5 Maryam Dastoorpoor,6 Nima Hajhashemi,7 Mitra Naseh,8 Shahnaz Rimaz9 1Department of Epidemiology, Robert Stempel College of Public Health and Social Work, Florida International University, Miami, FL, USA; 2Department of Biology, North Carolina Agricultural and Technical State University, Greensboro, NC, USA; 3Department of Kinesiology, College of Nursing and Health Innovation, University of Texas at Arlington, Arlington, TX, USA; 4Road Traffic Injury Research Center, Tabriz University of Medical Sciences, Tabriz, Iran; 5Department of Statistics and Epidemiology, Faculty of Health, Tabriz University of Medical Sciences, Tabriz, Iran; 6Department of Biostatistics and Epidemiology, Menopause Andropause Research Center, Ahvaz Jundishapur University of Medical Sciences, Ahvaz, Iran; 7Department of Biology, University of North Carolina at Greensboro, Greensboro, NC, USA; 8School of Social Work, Robert Stempel College of Public Health and Social Work, Florida International University, Miami, FL, USA; 9Radiation Biology Research Center, Department of Epidemiology, School of Public Health, Iran University of Medical Sciences, Tehran, IranCorrespondence: Shahnaz RimazRadiation Biology Research Center, Department of Epidemiology, School of Public Health, Iran of University of Medical Sciences, Shahid Hemmat Highway, Tehran 1449614535, IranTel +98- 21 86704645Email rimaz.sh@iums.ac.irBackground: Stigma against HIV profoundly affects the quality of life (QOL) of people living with HIV/AIDS (PLWHA). We aimed to assess the factors associated with QOL in PLWHA in Iran, specifically HIV-related stigma, sociodemographic and clinical characteristics.Methods: Two hundred PLWHA participated in this cross-sectional study. Data were collected using sociodemographic, stigma, and WHO-QOL-BREF questionnaires. Correlations, ANOVAs, and Student’s t-distribution tests were performed as bivariate analyses. We employed stepwise multiple linear regression analysis to explore the main factors associated with QOL domains.Results: Six domains of QOL were negatively correlated with three domains of stigma (p<0.001 for all). Stepwise multiple linear regression revealed that, after adjusting for confounders, lack of healthcare insurance, having no basic knowledge of HIV/AIDs prior to diagnosis, low monthly income of participants and family, and stigma (blaming and distancing, discrimination, and fear) were associated with low mean score of different domains of QOL.Conclusion: Our findings indicated that increasing HIV/AIDS-related stigma decreases QOL in PLWHA in Iran. Attention toward decreasing stigma, improving healthcare plan, and cultivating economic condition should be given high priority to ensure improvement in total QOL and corresponding domains in PLWHA’s life.Keywords: HIV, AIDS, quality of life, stigma, Iran